The CRL7FBXW8 Complex Controls the Mammary Stem Cell Compartment through Regulation of NUMB Levels - Simone Sabbioni; Maria Grazia Filippone; Letizia Amadori; Stefano Confalonieri; Roberta Bonfanti; Stefano Capoano; Ivan Nicola Colaluca; Stefano Freddi; Giovanni Bertalot; Giovanni Fagà; Elisa Zagarrí; Mario Varasi; et al. (Advanced Science)
Abstract NUMB is a tumor suppressor gene that functions by inhibiting the action of the NOTCH proto‐oncogene and enhancing the levels and activity of the tumor suppressor protein p53. In breast cancer (BC), NUMB loss of function (LOF), mediated by various molecular mechanisms, is a frequent and causal event. Herein, it is established that loss of NUMB protein, resulting from protein hyper‐degradation, is the prevalent mechanism of NUMB LOF in BC. Through an RNAi‐based screening, the CRL7FBXW8 complex is identified as the E3 ligase complex responsible for NUMB hyper‐degradation in BC. Genetic and pharmacological inhibition of CRL7FBXW8 rescues the transformation‐related phenotypes induced by NUMB LOF in BC cell lines and in patient‐derived xenografts. These effects are directly dependent on the restoration of NUMB protein levels. Thus, enhanced CRL7FBXW8 activity, through its interference with the tumor suppressor activity of NUMB, is a causal alteration in BC, suggesting it as a potential therapeutic target for precision medicine.